Solving the paradox of monetary profits - Steve Keen (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
Bruun and Heyn-Johnsen (2009) state the paradox that economics has failed to provide a satisfactory explanation of how monetary profits are generated, even though the generation of a physical surplus is an established aspect of non-neoclassical economics. They emphasise that our ability to explain phenomena like the Global Financial Crisis (GFC) will be limited while ever we are still unable to explain this fundamental aspect of capitalism. In fact this paradox can be solved very simply, using insights from what is known as 'Circuit Theory'. In this paper the author shows how monetary profits are generated, and uses a monetary circuit of production model to derive policy conclusions about how to overcome a 'credit crunch' that reverse the guidance given by the standard but empirically falsified 'money multiplier' model of credit money creation.
Keywords: E20; E51; E12; E17; 330; Endogenous money; circuit theory; credit crunch; Geldtheorie; Kredittheorie; Gewinn; Ungleichgewichtstheorie; Dynamisches Modell; Mehr-Sektoren-Modell; Theorie